PEMBUATAN ES KRIM RUMPUT LAUT (Phaeophyceae) (The Making Ice Cream Seaweed (Phaeophyceae)) (Jurnal Teknologi Pangan, 2015)
Abstract Ice cream is an emulsion o/w system. in the manufacture of ice cream can occur the formation of ice crystals in ice cream are rough which usually occurs due to freezing repeatedly. The formation of large ice crystals and a sandy texture that can be prevented by the addition of flour, seaweed, mostly contain karaginan. While adding the butter to form a soft texture that is the goal of this research is to know the influence of the addition of seaweed flour and butter in the manufacture of ice-cream are favored by consumers. The research design used is (Completely Random Design) with two factors, namely the addition of seaweed flour type of Brown algae (phaeophyceae), 5%, 10%, 15% and butter 2.5%, 5%, 7.5%.The results can be concluded that the addition of flour seaweed 5 % and butter 7.5 % results that favored the panel with levels of fat 35,34 %, levels of iod 0,0137 %, levels of coarse fiber 3,61 %, overrun 57,11 %, the texture of 94, a sense of 88,5 and color of 94.   Keyword : ice cream, seaweed flour, butter     Abstrak Es krim merupakan sistem emulsi o/w. Pada pembuatan es krim dapat terjadi pembentukan kristal es yang kasar dalam es krim yang biasanya terjadi karena pembekuan yang berulang-ulang. Pembentukan kristal es yang besar dan tekstur yang berpasir dapat dicegah dengan penambahan tepung rumput laut yang sebagian besar mengandung karaginan. Sedangkan penambahan mentega berfungsi untuk membentuk tekstur yang lembut Tujuan dari Penelitian ini adalah untuk mengetahui pengaruh penambahan tepung rumput laut dan mentega dalam pembuatan es krim yang disukai oleh konsumen. Rancangan penelitian yang digunakan adalah RAL (Rancangan Acak Lengkap) dengan 2 faktor yaitu Penambahan tepung rumput laut jenis ganggang coklat (phaeophyceae), 5%, 10%, 15% dan mentega 2,5%, 5%, 7,5%. Hasil Penelitian dapat disimpulkan bahwa penambahan tepung rumput laut 5% dan mentega 7,5% memberikan hasil yang disukai panelis dengan kadar lemak 35,34%, kadar iod 0,0137%, Kadar serat kasar 3,61%, Overrun 57,11%, tekstur 94, rasa 88,5 dan warna 94.   Kata kunci : es krim, tepung rumput laut, mentega